2012
DOI: 10.1590/s1517-83822012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal antibiotic-phytochemical combinations against methicillin resistant Staphylococcus aureus

Abstract: Methicillin resistant Staphylococcus aureus (MRSA) infection is a global concern nowadays. Due to its multi-drug resistant nature, treatment with conventional antibiotics does not assure desired clinical outcomes. Therefore, there is a need to find new compounds and/or alternative methods to get arsenal against the pathogen. Combination therapies using conventional antibiotics and phytochemicals fulfill both requirements. In this study, the efficacy of different phytochemicals in combination with selected anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 6 publications
3
35
0
Order By: Relevance
“…While Q + M + R with AMP and AMO showed additive effect (FICI <1). These results are in in conformity with earlier findings where quercetin was found to be synergistic with minocycline, fusidic acid and rifampicin [24]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While Q + M + R with AMP and AMO showed additive effect (FICI <1). These results are in in conformity with earlier findings where quercetin was found to be synergistic with minocycline, fusidic acid and rifampicin [24]. …”
Section: Discussionsupporting
confidence: 93%
“…Quercetin alone has been found active against S. aureus and K. pneumoniae [23]. It has also been found to be potentiating effects of antibiotics such as rifampicin, fusidic acid and rifampicin against MRSA and MSSA [24]. Quercetin alone and in combination with gentamycin, levolfloxacin and sulphadiazine was found to be synergistic since MIC of qurecetin and test antibiotics decreased four folds when they were combined with each other [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Kyaw and Lim (2012) which reported that eugenol which is a bacteriostatic phytochemical (Rastogi et al, 2008;Yadav et al, 2015) in combination with a bacteriostatic antibiotic minocycline produced indifference interaction. According to Qin et al (2013), indifference is when the combined action is the same as with either component alone.…”
Section: Discussionsupporting
confidence: 87%
“…One approach using combination of antimicrobial therapy that consists of existing antibiotic and plant extract is the best alternative therapeutic weapon to combat superbug pathogen (Cowan, 1999;Kyaw and Lim, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently employed is the checkerboard assay, which expresses antimicrobial interactions on the basis of the fractional inhibitory concentration index (FICI) or isobolograms [7,10]. There are different interpretations of antimicrobial interactions on the basis of FICI, for example a synergistic interaction is considered to occur if FICI ≤ 0.5 [11,12,13] or < 1 [2]. There are also different interpretations of the FICI values denoting additivity (0.5 < FICI ≤ 1, FICI = 1) [2,11,12], indifference (1 < FICI ≤ 2, 1 < FICI ≤ 4, 5 < FICI ≤ 4) [11,12,13,14] and antagonism (FICI > 1, 2 or 4) [2,11,12,13].…”
Section: Introductionmentioning
confidence: 99%